Price Perceptions and Consumer Shopping Behavior: A Field Study - Lichtenstein, Donald R.; Ridgway, Nancy M.; Netemeyer, Richard G. (Journal of Marketing Research, 1993)
Seven price-related constructs—five consistent with a perception of price in its “negative role” and two consistent with a perception of price in its “positive role”— are used as independent variables to predict marketplace responses/behaviors in five domains: price search, generic product purchases, price recall, sale responsiveness, and coupon redemption. The price-related constructs explain a significant amount of variance in all five domains, providing evidence of predictive validity. Results of a higher order factor analysis are also reported, which provide some support for the positive-negative perception of price taxonomy.